Efeitos da antropização da zona costeira sobre as assembléias de aves - Mäder, Aurélea (Universidade do Vale do Rio do Sinos, 2010)
Urbanized areas negatively affect the distribution, abundance and behavior of coastal waterbirds. In this study we tested the hypothesis that coastal areas disturbed by man (1) has a lower abundance and diversity of birds, (2) differentiation in species composition and (3) presents a different temporal pattern of abundance of undeveloped coastal areas. For this, we use 16 sub-areas on the coast of Rio Grande do Sul (8 non-urbanized and urbanized 8). 73 893 birds were recorded in the study, these 46 295 (63%) individuals were recorded on the coast average (non-urbanized) and 27 598 (37%) on the north coast (urbanized). Richness was similar between the two areas, but the amount of individuals that occurred on the beaches differed significantly. Nearctic migratory birds, as well as representatives of the order sub-orders Scolopaci and Lari are more abundant in the coastal average, while Ciconiiformes, Falconiformes and Passeriiformes are mostly found in the north coast. We observed a significant increase for som
Keywords: áreas urbanizadas; aves aquáticas costeiras; urbanized areas; coastal waterbirds; Ciências Biológicas